Pemulihan Layanan Melalui Customer Affection Pada Kepuasan Penanganan Keluhan Mitra Pengemudi Online - Isti Riana Dewi; Ni Wayan Fitriana Ayu Lestari; Dewi Anggun Puspitarini (JURNAL MANEKSI, 2021)
Complaints from online driver-partners against online transportation companies tend to occur frequently about the services provided. Online transportation companies are required to reduce service failures that occur. The complaints from the driver-partners themselves are seen to have fluctuated. However, the complaints that occur do not prevent new enthusiasts from joining as partners. The purpose of this study was to determine the effect of service recovery on complaint handling satisfaction and customer affection as a mediator. The unit of analysis is Grab driver who visited the Banyumas service office during the past year. The number of respondents in this research is 204, the questionnaire as an instrument, and the analysis technique uses Structural Equation Modeling. The results found that there is a positive effect of distributive justice, procedural justice, and interactional justice on the satisfaction of online driver-partners. Then, distributive justice, procedural justice, and interactional justice have a positive effect on online driver-partner satisfaction mediated by customer affection.